Mirror World, Minus World. - Ferguson, Andrew (Textual Cultures: Text, Contexts, Interpretation (Indiana University Press))
This article considers different experiences available to the reader of Vladimir Nabokov's Pale Fire by exploring the novel through concepts familiar from videogaming, such as the warp, the glitch, and the Let's Play, developing particular parallels with the Nintendo game Super Mario Bros. All of these potential modes of experience are comprised in the playerly text, which serves as a conduit linking together a work's past, present, and future readers.